Lateralidad y sentido de giro en gimnasia artística y patinaje artístico - Merino Montejo, J. J. (Universität Leon, 2018)
In this research, laterality is studied in subjects of school age. Observational methodological tests are applied in extracurricular physical activities, artistic gymnastics and figure skating. It raises the hypothesis of relating the monopodal and oculus-auditory dominance tests with the specific tests for the observation of the preferred or directional leg in the previous activities. We work with 43 subjects, 10 boys and 33 girls, between ages 4 and 12 years; 18 practice artistic gymnastics, 29 figure skating and 4 both. We applied the Harris test (1957), resulting in 6 right-handed subjects completely affirmed, the others presented no affirmed laterality; and the Mayolas test (2003) that results in 3 completely right-handed subjects, 1 left-handed with probably crossed laterality, while rest shows different results. According to the modified test of Carrasco (1972) applied to 18 subjects, 4 are right-footed, 3 twist on right and only two subjects twist on the direction of the support foot. Regarding the modified skating test, of the total of 29 subjects, 23 were right-handed, 1 left-footed and 13 and 5 subjects present a coefficient of twist to right and left respectively.